FORMULATION AND IN VITROEVALUATION OF FLOATING TABLETS OF CEFPODOXIME PROXETIL - Tekade, Bharat W.; Jadhao, Umesh T.; Patil, Shruti G.; Patil, Vijay R. (International Journal of Current Pharmaceutical Research, 2017)
Objective: The objective of research work was to formulate and evaluate the floating drug delivery system containing Cefpodoxime Proxetil using polymer HPMC K4M, Guar Gum. Methods: Effervescent floating tablets containing Cefpodoxime proxetil were prepared by direct compression technique using varying concentrations of different grades of polymer. Results: Physical parameters like hardness, weight variation, thickness and friability were within pharmacopoeial limit. Percentage drug content in all floating tablet formulations was found to be 90% to 110%. The floating time was found to be more than 12 H. floating lag time was found to be 10Â±2.99 second. Formulation batch F8 was selected as an optimum formulation, as possessing less disintegration time, higher water absorption ratio and good content uniformity i.e. within acceptable limit.% drug release of formulation batch F8 was found to be 96.66% in 0.1 N HCL. Conclusion: The FT-IR studies of batch F8 was carried out which showed the peak values within the spectrum corresponding to the peak values of pure drug.